Irrevocable belief revision and epistemic entrenchment - Fermé, E. (2021)
In recent papers [10, 11] Krister Segerberg introduced Irrevocable Belief Revision, as closely related to AGM revision [2]. In this paper we present irrevocable belief revision in terms of an epistemic entrenchment relation.1